Crystallization characteristics of isotactic polypropylene with and without nucleating agents - Kim, Y.C.; Kim, C.Y.; Kim, S.C. (1991)
Nucleation effects of two sorbitol derivatives on the crystallization of isotactic polypropylene (iPP) were studied by means of differential scanning calorimetry (DSC) and polarized optical microscopy (POM). A nonisothermal crystallization kinetic equation was employed to analyze the crystallization characteristics of iPP with or without the nucleating agents from DSC crystallization thermograms. The equilibrium melting temperature of iPP necessary for the kinetic study was obtained by the extrapolation method to be 209°C. The nonisothermal crystallization kinetic analysis for the unnucleated iPP at different cooling rates was possible by assuming the spherulite growth initiated simultaneously by heterogeneous and homogeneous nucleation. On the other hand, the crystallization kinetics of the nucleated iPP could be described by the heterogeneous nucleation and growth process alone. The addition of the nucleating agents up to their saturation concentrations in iPP increased the crystallization peak temperature by 17°C, and the number of effective nuclei by three orders of magnitude. A high concentration of the nucleating agents caused agglomeration of the agents to lower the number of effective nuclei. Copyright ？ 1991 Society of Plastics Engineers